UKRAINIAN POSTCOLONIAL NOVEL AS A NATIONAL NARRATIVE: “THE MUSEUM OF ABANDONED SECRETS” BY O. ZABUZHKO AND “THE BEECH LAND” BY M. MATIOS - Kateryna V. Butska (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article examines the seminal novels of Ukrainian women writers from the first and second decades of the 21st century, namely “The Museum of Abandoned Secrets” (“Музей покинутих секретів”, 2009) by O. Zabuzhko and “The Beech Land” (“Букова земля”, 2019) by M. Matios. The selected works are analyzed through the lens of postcolonial criticism, that is, from the point of view of the historical experience of the statelessness of the Ukrainian community and its reflection in literary texts. The main attention is paid to the narrative features of the works, namely the tendency to broad narrative, integrity, and narrative completeness. The purpose of the study is to highlight the postcolonial content of the narrative strategies implemented in the selected novels by O. Zabuzhko and M. Matios. Given that “The Museum of Abandoned Secrets” and “The Beech Land” represent different periods and ideological and aesthetic paradigms, namely postmodernism and metamodernism, one of the tasks of the study is to assert the relevance of postcolonialism in the context of metamodernism. The article aims to highlight the peculiarities of the artistic realization of “postcolonial” narrativity in postmodern and metamodern texts. Additionally, the narrative features of the selected novels are compared. The stated purpose necessitates the application of hermeneutic (interpretation of a literary text), comparative (identification of common and distinctive features of the selected works) methods, as well as the method of structural analysis (examining the narrative structure of the texts). As a result of the study, it is established that postcolonialism, inherent in Ukrainian postmodern prose, remains relevant in the second decade of the twenty-first century. The postcolonial orientation of the novels “The Museum of Abandoned Secrets” and “The Beech Land” is manifested in their intention to affirm the continuity of Ukrainian history by building a panoramic narrative that covers different historical periods and establishes a hereditary connection between them. The study identified the following features common to both novels: the intertwining of family genealogy with national history; the development of narratives at different generational levels – children, parents, grandparents, etc.; the theme of the perpetual war for independence that continues to this day; the image of God as a transcendent guardian of history, capable of seeing the intertwining of human destinies in their entirety. The defining theme shared by both novels is the anti-colonial struggle, particularly the military campaign of the Ukrainian Insurgent Army. This theme necessitates depicting the tragic consequences of imperial oppression. In “The Beech Land”, these are devastation and turmoil, fratricide, ruptured familial ties, the destruction of the Bukovynian “utopia”. In “The Museum of Abandoned Secrets”, these repercussions are shown through the lens of postmodern hypertextuality – as “burnt manuscripts”, irretrievably lost archives, fragmented stories. In addition, the selected novels exhibit an inclination to transcend the boundaries of realistic storytelling. Employing the montage technique, “The Museum of Abandoned Secrets” incorporates a mystical discourse of dreams that operates as a parallel reality, recounting events of the past. The oneiric discourse resonates with the image of an endless virtual archive storing memories of everything that has ever happened in the world. In “The Beech Land”, the departure from realistic historiography occurs through metamodern fantastisation, where the historical panorama is framed by the story of the “Heavenly Chancellery” – a celestial archive inhabited by the Creator and the Angels. The appeal to mystical and imaginative discourses is interpreted as a manifestation of postcolonial longing for lost integrity and completeness. The images of endless imaginary repositories of information complement the incompleteness of history, aiding in overcoming its fragmentary nature and opacity.